REPRESENTAÇÕES E ATITUDES LINGUÍSTICAS NA (RE)CONSTRUÇÃO DA IDENTIDADE INDÍGENA DOS GUARANI DO PINHALZINHO (TOMAZINA/PR): UM ESTUDO NA ESCOLA “YVY PORÃ” - Kondo, Rosana Hass (2013)
This study aims to investigate the relationship established between linguistic representations and attitudes - about languages and cultures present in the community - and (re) construction of indigenous identity on the Guarani village Pinhalzinho, Tomazina, Paraná, in such a way that the community can, from a greater understanding of yourself, envision ways to build language policies to enable a fact-specific education that meets their needs, desires and rights. Through it we discuss some aspects related to indigenous identity, representation of indigenous identity and indigenous teacher training, specifically how they are situated on the requirement to achieve a specific, differentiated, intercultural and bilingual education (RCNEI, 1998). Info analysis on this dissertation gather data generated from observations, semi structured interviews (recorded in audio and video), field diary and collected ethnographic interventions (Ludke; ANDRÉ, 1986). This is a qualitative/interpretive research with proposed intervention (ANDREW, 1995; TELLES, 2002; BARBIER, 2007; Thiollent, 2011), since our goal was not simply to collect and verify data, but also from them doing research on the needs and desires of the community with regard to the Guarani language and other spoken languages in the region and ways to (re) define what means being Indian (Maher, 1996) in current society, and later, together with the indigenous community, discuss and reflect on proposals and actions that can support teachers work in the classroom in a way that designed education can prepare this indigenous community to face political conflict that may come from the dominant society. Altogether participants were fourteen (14) persons, which play important roles in the community and/or school, namely: one (01) member of the indigenous community leadership and school Yvy Pora, two (02) teaching staff members, two (02) Indigenous teachers, four (04) non-Indigenous teachers and five (05) Indigenous students. The theoretical apparatus that has underpinned work was guided by the contributions of Applied Linguistics researchs as (CESAR, Cavalcanti, 2007; MAHER, 1996, 1998, 2007a, 2007b), Cultural Studies (Hall 1997; WOODWARD, 2009), Anthropology (CUCHE, 1999; MOTA, 1994, 2006), among others. Obtained results from this data analysis suggest that: a) Indian education (school) has great influence on the formation of leaders and active critics both in the indigenous community as well in the non-indigenous society, b) there is lack of autonomy and as well vertical integration of educational policies, that is, the aspects of education are not being built in conjunction with the community, c) there is no specific continuing education for indigenous and non-indigenous teachers d) the attitude of the State Department of Education and some non-indigenous teachers about language, culture and identity are often ethnocentric, e) Guaranies have representation about language, culture and indigenous identity that are influenced by ideas that non-indigenous people elected as defining criteria for such. Our expectation is that this research can support the work of teachers (indigenous and non-indigenous) to build a committed to education with their needs and desires, teachers with intercultural curriculum that can enable the Guarani voices to be present in society that can at least to reduce the exclusion process of which this minority group has been victim.